Relationship Between law Positions and Cranial Base Angle - Güvenç Başaran; Törün Özer; Orhan Hamamcı (Galenos Yayinevi, 2006)
Cranial base flexure has long been of interest to orthodontists. This indicates that the cranial base flexure may or may not have an effect on the facial prognathism and classification of malocclusions. The present study evaluates the correlation of cranial base flexure and craniofacial pattern. The sample consisted of 150 individuals from 5 different malocclusion groups. Records were matched for age and sex as far as possible. ANOVA test was used to investigate intergroup variability. The group means were compared by independent t test. Intervariable correlations were also compiled. Cranial base angle does not appear to have an important role in determining malocclusion.